Strengthening local government policies to address health inequities: perspectives from Australian local government stakeholders - Sally Schultz; Christina Zorbas; Anna Peeters; Serene Yoong; Kathryn Backholer (BMC, 2023)
Abstract Background With their close connection to community and increasing preventive health remit, local governments are well positioned to implement policies and programs to address health inequities. Nevertheless, there is a lack of evidence of equity-focused policy action in this sector. We aimed to understand how local government representatives approach equity in the development and implementation of health and wellbeing policies and programs, and to identify potential enablers for strengthening an equity focus. Methods We conducted semi-structured interviews (June 2022-January 2023) with 29 health directorate representatives from 21 local governments in Victoria, Australia. Representatives were recruited from urban, regional and rural local government areas, with varying levels of socioeconomic position. Data was analysed inductively using Braun and Clarke's reflexive thematic analysis, informed by social determinants of health theory and a public policy decision making framework. Results Local governments approach health equity in different ways including focusing on priority populations, disadvantaged geographic areas, or by targeting the upstream determinants of health, such as housing and employment. Enabling factors for more equity-oriented local government policy action included those internal to local governments: (i) having a clear conceptualisation of equity, (ii) fostering a strong equity-centric culture, and (iii) developing organisational-wide competency in health equity. External factors related to key stakeholder groups that support and/or influence local governments included: (iv) strong support from community, (v) state government leadership and legislation, and (vi) supportive local partners, networks and NGO's. Conclusions Local governments have a responsibility to implement policies and programs that improve health and reduce health inequities. Local government's capacity to leverage resources, structures, processes and relationships, internally and across sectors and community, will be key to strengthening equity-oriented local government health policies and programs.